Impact of lightning on tower footing design of 500 kV transmission line - Mohd Nasir, N. A. F.; Mohd Nasir, M. S.; Abd Rahman, Muhamad Safwan; Ab-Kadir, M. Z. A.; Azis, N.; Osman, M.; Ungku Amirulddin, Ungku Anisa (IEEE, 2023)
This study evaluates several tower earthing designs for improving 500 kV transmission line’s lightning performance and ensure its continuous operation. The study includes the assessment of the soil profile and a comparison of the findings obtained using the default and new earthing arrangement, both of which are intended to improve the tower footing resistance (TFR-during steady-state) and tower footing impedance (TFI-during lightning). Assessment of the TFR and TFI has been performed before and after the earthing design improvement. In addition, the impacts of these TFR and TFI, which are also defined as low and high-frequency earthing, respectively, relying on a specification of TFR and soil resistivity (SR) ranges at different locations have also been taken into consideration. The study was performed with the help of the SESCAD tool of Current Distribution Electromagnetic Field Grounding and Soil Structure Analysis program (CDEGS), as well as the PSCAD/EMTDC software, which was used for low and high frequency earthing, accordingly. Upon the completion of the investigation, the findings revealed that the modification to the earthing arrangement had a beneficial effect on lowering the TFR by 84.29 % and 88.34 % for Towers T41 and T42, respectively. While for TFI, the results revealed a significant decrease below the TFR during high frequency operation, which was attributed to soil ionization process that occur due to lightning. This was proved by the fact that the values were significantly below the TFR. All these enhancements are now being explored and evaluated across all of Malaysia’s 500 kV networks, where lightning is regarded to be the primary risk factor for power outages.